Local recurrence of tumor at sites of intervention in malignant pleural mesothelioma - BATIREL, HASAN FEVZİ (ELSEVIER IRELAND LTD, 2008)
In malignant pleural mesothelioma (MPM) patients, local. dissemination (LD) of the tumor is frequently observed at the sites of intervention where diagnosis/treatment are performed. We evaluate the factors affecting LD frequency and discuss the use of PR in MPM patients. Histopathotogically diagnosed 212 MPM patients who had not received PR were evaulated in terms of development of LD. Of the 212 patients, 29 received supportive therapy, 157 received chemotherapy and 26 received multi-modal therapy. The LD frequency was 13.2% for all patients. The median survival rate was 9 or 10 months in patients with or without LD, respectively. A higher LD frequency was observed in patients receiving thoracotomy. The LD appearance time in supportive care is short. The LD frequency in patients treated with chemotherapy that revealed progressive disease was higher than the patients who revealed stable disease or objective response. LD developed in 2 months in patients with sarcomatous and mixed cell type, and the survival rate was low. LD was not associated with the stage of the disease. The most suitable candidate groups for PR are patients receiving supportive therapy, thoracotomy without multi-modal therapy or patients with sarcomatous and mixed cell type tumors. (C) 2008 Elsevier Ireland Ltd. All rights reserved.
Keywords: mesothelioma; radiotherapy; diagnose; therapy; SUBCUTANEOUS IMPLANTATION; RANDOMIZED-TRIAL; RADIOTHERAPY; PREVENTION; BIOPSY; CHEMOTHERAPY; SURVIVAL; THERAPY; CANCER